Descriptive analysis of core services outcomes in Larimer County: final report - Winokur, Marc, author; Social Work Research Center, Colorado State University, publisher (Colorado State University. Libraries, 2006)
Child welfare agencies traditionally have struggled with how to integrate the diverse service and placement options they provide to more effectively and efficiently serve children and families. This study employed a between-groups design to compare the child welfare outcomes of children in Larimer County. According to the results, many of the services offered by the Larimer County Department of Human Services are associated with positive child welfare outcomes. An argument can be made that integrated service delivery appears to be effective for some Core Services in improving the safety, permanency, and well-being of children and families in Larimer County.
December 2006.
Keywords: Child welfare -- Government policy -- Colorado -- Larimer County